2020
DOI: 10.1186/s13075-020-2095-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of performance of specific (SLEQOL) and generic (SF36) health-related quality of life questionnaires and their associations with disease status of systemic lupus erythematosus: a longitudinal study

Abstract: Background: The utility of generic health-related quality of life (HRQoL) questionnaires in patients with systemic lupus erythematosus (SLE) is uncertain. We compared the performance of generic (SF36) and specific (SLEQOL) HRQoL surveys by examining their associations with the Global Rating of Change (GRC) and SLE clinical indicators. Methods: The study included SLE patients who attended a single-center rheumatology clinic between 2013 and 2017. Patients completed both specific (SLEQOL) and generic (SF36) surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 45 publications
(72 reference statements)
4
34
2
1
Order By: Relevance
“…Although the relationship between disease activity and HRQoL in SLE is still controversial [9,26,27], some recent data from the literature would seem to demonstrate a positive impact of the conditions of remission/LLDAS on patients' HRQoL [28], in contrast with our findings. In any case, the results of some of these recent studies are not comparable with this study due to some important differences in the populations included in contrast with our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the relationship between disease activity and HRQoL in SLE is still controversial [9,26,27], some recent data from the literature would seem to demonstrate a positive impact of the conditions of remission/LLDAS on patients' HRQoL [28], in contrast with our findings. In any case, the results of some of these recent studies are not comparable with this study due to some important differences in the populations included in contrast with our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Continuous variables were compared using the Mann-Whitney U test, and categorical variables using the chi-squared test. Longitudinal data was analyzed using generalized estimating equations (GEE) [31][32][33], Wilcoxon signed rank sum test, repeated measures analysis of variance (ANOVA), and post hoc test. For GEE, the number of peripheral immune cells were normalized using z-score.…”
Section: Discussionmentioning
confidence: 99%
“…This may be achieved through remission and low-disease activity. While a single main definition of low disease activity [the lupus low disease activity state (LLDAS)] has emerged [ 73 ], various definitions for remission have been proposed by different groups [ 74 , 75 ] and the optimal one remains to be determined. Several studies have shown that the risk of damage decreases with the length of time in either LLDAS or remission.…”
Section: Long-term Outcomes In Sle: Trends Over Time and Major Contrimentioning
confidence: 99%